A Simulation-Based Quality Improvement Initiative Improves Pediatric Readiness in Community Hospitals. Issue 6 (June 2018) - Whitfill, Travis; Gawel, Marcie; Auerbach, Marc
Abstract : Background: The National Pediatric Readiness Project Pediatric Readiness Survey (PRS) measured pediatric readiness in 4149 US emergency departments (EDs) and noted an average score of 69 on a 100-point scale. This readiness score consists of 6 domains: coordination of pediatric patient care (19/100), physician/nurse staffing and training (10/100), quality improvement activities (7/100), patient safety initiatives (14/100), policies and procedures (17/100), and availability of pediatric equipment (33/100). We aimed to assess and improve pediatric emergency readiness scores across Connecticut's hospitals. Objective: The aim of this study was to compare the National Pediatric Readiness Project readiness score before and after an in situ simulation–based assessment and quality improvement program in Connecticut hospitals. Methods: We leveraged in situ simulations to measure the quality of resuscitative care provided by interprofessional teams to 3 simulated patients (infant septic shock, infant seizure, and child cardiac arrest) presenting to their ED resuscitation bay. Assessments of EDs were made based on a composite quality score that was measured as the sum of 4 distinct domains: (1) adherence to sepsis guidelines, (2) adherence to cardiac arrest guidelines, (3) performance on seizure resuscitation, and (4) teamwork. After the simulation, a detailed report with scores, comparisons to other EDs, and a gap analysis were provided to sites. Based on this report, a regional children's hospital team worked collaboratively with each ED to develop action items and a timeline for improvements. The National Pediatric Readiness Project PRS scores, the primary outcome of this study, were measured before and after participation. Results: Twelve community EDs in Connecticut participated in this project. The PRS scores were assessed before and after the intervention (simulation-based assessment and gap analysis/report-out). The average time between PRS assessments was 21 months. The PRS scores significantly improved 12.9% from the first assessment (mean ± SEM = 64 ± 4.4) to the second assessment (77 ± 4.0, P = 0.022). The PRS score domains also showed improvements in coordination of pediatric patient care (median improvement, 50%), quality improvement activities (median improvement, 79%), patient safety initiatives (mean improvement, 7%), policies and procedures (mean improvement, 17%), and availability of pediatric equipment (mean improvement, 7%). Conclusions: Participation in a simulation-based quality improvement collaborative was associated with improvements in pediatric readiness.